PENYELESAIAN RAPAT UMUM PEMEGANG SAHAM DALAM PENGAMBILAN KEPUTUSAN DENGAN JUMLAH SUARA YANG BERIMBANG PADA PT. BALI BIAS PUTIH - Vindiata Candra Dewi, Luh Putu; Wairocana, I Gusti Ngurah (Kertha Semaya : Journal Ilmu Hukum, 2014)
This paper based on an impartial ownership vote on PT. Bali Bias Putih which is located in Tabanan, until lead to deadlock in decision making of Annual General Meeting (AGM) has a purpose to understand how to settlement Annual General Meeting (AGM) on decision making with an impartial ownership vote on PT. Bali Bias Putih. The research method used in this study is an empirical research, with a result that a decision can be taken by court order if Annual General Meeting (AGM) does not produce any results.
Keywords: AGM, decision, court order